1996
DOI: 10.1182/blood.v87.7.2675.bloodjournal8772675
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human erythropoietin in transfusion-dependent anemic patients with multiple myeloma and non-Hodgkin's lymphoma--a randomized multicenter study. The European Study Group of Erythropoietin (Epoetin Beta) Treatment in Multiple Myeloma and Non-Hodgkin's Lymphoma

Abstract: One hundred twenty-one anemic, transfusion-dependent patients with multiple myeloma (MM) or low-grade non-Hodgkin's lymphoma (NHL) were randomly allocated to receive (a) recombinant human erythropoietin (rhEPO) 10,000 U/d subcutaneously 7 days a week (fixed dose group) (n = 38), or (b) rhEPO 2,000 U/d subcutaneously for 8 weeks followed by step- wise escalation of the rhEPO dose (titration group) (n = 44), or (c) no rhEPO therapy (control group) (n = 39). The total treatment period was 24 weeks. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(66 citation statements)
references
References 25 publications
(1 reference statement)
1
57
0
6
Order By: Relevance
“…More recent research with rHuEPO has focused on the identification of variables that are predictive of future response to therapy. These include baseline variables such as serum ferritin, serum erythropoietin levels, and baseline Hb levels, as well as early response variables [26][27][28][29]. However, results have yet to demonstrate clinical sensitivity and specificity in prognosticating response to rHuEPO [30].…”
Section: For Reprints Contact: Reprints@alphamedpresscommentioning
confidence: 99%
“…More recent research with rHuEPO has focused on the identification of variables that are predictive of future response to therapy. These include baseline variables such as serum ferritin, serum erythropoietin levels, and baseline Hb levels, as well as early response variables [26][27][28][29]. However, results have yet to demonstrate clinical sensitivity and specificity in prognosticating response to rHuEPO [30].…”
Section: For Reprints Contact: Reprints@alphamedpresscommentioning
confidence: 99%
“…Based on a systematic review of the literature, the recent guidelines of the American Society of Clinical Oncology and the American Society of Hematology (Rizzo et al, 2002) recommend use of epoetin as a treatment option for patients with chemotherapy-associated anaemia with a haemoglobin concentration below 10 g/dl, and advise subcutaneous administration thrice weekly at a starting dose of 150 U/kg. Three European trials in the last few years have studied the efficacy of epoetin beta in anaemic patients with multiple myeloma, non-Hodgkin's lymphoma and chronic lymphocytic leukaemia, most of whom were receiving concurrent or recent chemotherapy for their disease (Cazzola et al, 1995;Osterborg et al, 1996Osterborg et al, , 2002. Despite considerable differences in their designs, all three studies showed that defective endogenous Epo production was a major predictor of response to treatment.…”
mentioning
confidence: 99%
“…In patients with solid tumors, the adverse event profiles were similar in the rHuEPO and placebo groups, though a few more cases of deep vein thrombosis occurred in the rHuEPO group. In six trials in patients with anemia due to an underlying hematologic malignancy [68][69][70][71][72][73], there was a statistically significant higher rate of hypertension (10% versus 1%; p = .011) and a nonsignificantly higher rate of thromboembolic events (3% versus 0%; p = .55) among rHuEPO-treated patients [11]. The incidences of adverse events were similar in three community-based, open-label trials [38][39][40] and generally lower than those reported in the comparative trials.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%